Basal cell adhesion molecule/lutheran protein. The receptor critical for sickle cell adhesion to laminin. - Udani, M; Zen, Q; Cottman, M; Leonard, N; Jefferson, S; Daymont, C; Truskey, G; Telen, M J (The Journal of Clinical Investigation, 1998)
Sickle red cells bind significant amounts of soluble laminin, whereas normal red cells do not. Solid phase assays demonstrate that B-CAM/LU binds laminin on intact sickle red cells and that red cell B-CAM/LU binds immobilized laminin, whereas another putative laminin binding protein, CD44, does not. Ligand blots also identify B-CAM/LU as the only erythrocyte membrane protein(s) that binds laminin. Finally, transfection of murine erythroleukemia cells with human B-CAM cDNA induces binding of both soluble and immobilized laminin. Thus, B-CAM/LU appears to be the major laminin-binding protein of sickle red cells. Previously reported overexpression of B-CAM/LU by epithelial cancer cells suggests that this protein may also serve as a laminin receptor in malignant tumors.